Emotions and Risky Technologies
XXXII, 262 p.
Keywords: By offering an innovative and challenging approach to the topic of risk and emotion, this book covers completely new territory. It focuses on risk and emotion from the perspective of moral philosophy and emphasizes that emotions are an important source of moral knowledge. The book connects to important debates about risk and emotion in empirical decision theory. However, whereas in these debates, emotions are mainly seen as a threat for rational decision making, this book investigates the novel idea that emotions might be a normative guide in making judgments about morally acceptable risks. Technological risks such as cloning, GM-foods, and nuclear energy spark heated and emotional debates. Many people are afraid of the possible unwanted consequences of such technologies. This gives rise to the following normative question: do we need emotions in order to be able to judge whether a technology and its concomitant risks are morally acceptable? This question has direct practical implications: should engineers, scientists and policy makers involved in developing risk regulation take emotions (of the public, but also their own) seriously or not? This book sets the stage for research into moral emotions and risky technologies. It brings together leading scholars who work in the areas of risk perception, moral emotions, and ethics of risk, and lets them reflect on this exciting and important new topic. The book should be of interest for everybody involved with risk regulation, both at an academic and a practical level.